Measures of Spatial Population Distribution in Morogoro Region - Hamisi, Salum Haji (International Journal of Geography and Geology, 2022)
Measuring the spatial distribution of populations has been a complex process and has been a concern of demographers, researchers, geographers, and academics around the world. This paper attempts to take a step forward by consciously taking it. It is a very complex undertaking because it involves facts from the population or the study area. And in practice in developing countries, the facts or practical information are hard to come by. The paper objectively focuses on measuring the extent of population distribution in the Morogoro region using the approaches of Otis (1957). The study was intended to provide a basis for planning for policymakers, governments, non-governmental organisations and community-based organisations. The methodology chosen in this paper is an exhaustive documentary analysis, as the data on this type of study is almost always credible and available to the public. Extensive use of secondary data was used. After review, recalculation, preliminary discussion and recast; the region’s population has been shown to be unequally distributed, less concentrated in one settlement and less dense per square kilometre, even below the national average of 51 inhabitants per square kilometre. It suggests an uneven distribution of resources, making parts of the region populated and others less populated. Government has a role to play in ensuring that population distribution reflects available resources. Every measure selected and applied has some challenges or shortcomings, whether it is the availability of data or the accuracy of the tool.